GROWTH AND HERBAGE YIELD OF SETARIA SPHACELATA GRASS IN RESPONSE TO VARYING CLIPPING STAGES - M. Mushtaque; M. Ishaque; M. Ahmad alias Haji A. Bukhsh (Journal of Animal and Plant Sciences, 2010)
Setaria sphacelata is an aggressive perennial grass of arid tropical habitats around the globe. It prefers very warm climate and is restricted to these tropical environments. It was studied for its growth and herbage yield during early summer in 2003. Grass nursery of this plant was raised through its stubbles on a site having sandy loam to loam soil with a pH of 7.85 in plot size 1m x 3m. The experiment was carried out in complete randomized design with four replications. Four clipping stages i.e. CS1, CS2, CS3 and CS4 (clipped after 1, 2, 3 and 4 months, respectively) were studied. Data on morphological characters and herbage yield were recorded with delayed clipping stages (plant maturity), plant height, tiller density and basal circumference of the grass increased (P<0.05) while its leaf to stem ratio showed a decline. Herbage yield (fresh biomass, dry matter yield and organic matter yield) of the grass increased (P<0.05) as grass reached maturity. At later stage of plant maturity, the grass had lower vegetative parts than at the early stages of plant maturity. This study concluded that in order to get optimum biomass and sustained grass vigor; three months clipping stage should be recommended on this grass species.
Keywords: Setaria sphacelata; clipping stage; herbage yield; vegetative growth